2007
DOI: 10.1890/06-1585
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Competition via Induced Resistance: Specialist Herbivores Indirectly Suppress Generalist Preference and Populations

Abstract: Species may compete indirectly by altering the traits of a shared resource. For example, herbivore-induced responses in plants may make plants more resistant or susceptible to additional herbivorous insect species. Herbivore-induced plant responses can significantly affect interspecific competition and herbivore population dynamics. These herbivore-herbivore indirect interactions have been overlooked in aquatic ecosystems where previous studies used the same herbivore species to induce changes and to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 41 publications
4
60
0
Order By: Relevance
“…While all the grazers except the suspension feeding Caprella removed epiphytes, Idotea also appeared to remove eelgrass tissue from the surface of the leaves. Other studies have found variation in defense responses resulting from differences in feeding modes; e.g., the gastropod Littorina obtusata excavated brown algal tissues rather than removing entire portions of tissue like L. littorea, and only the former reduced palatability of the algae to multiple species [22]. Similarly, we found Ampithoe damage to leaf margins and removal of whole portions of eelgrass tissue to not induce a defense response in the plant.…”
Section: Mesocosm Experimentssupporting
confidence: 59%
See 1 more Smart Citation
“…While all the grazers except the suspension feeding Caprella removed epiphytes, Idotea also appeared to remove eelgrass tissue from the surface of the leaves. Other studies have found variation in defense responses resulting from differences in feeding modes; e.g., the gastropod Littorina obtusata excavated brown algal tissues rather than removing entire portions of tissue like L. littorea, and only the former reduced palatability of the algae to multiple species [22]. Similarly, we found Ampithoe damage to leaf margins and removal of whole portions of eelgrass tissue to not induce a defense response in the plant.…”
Section: Mesocosm Experimentssupporting
confidence: 59%
“…Several studies have demonstrated a negative correlation between concentration of phenolic compounds in seagrass and herbivory on it [20,21]. On marine algae, invertebrates have been found to induce defenses, which can influence interspecific competition among herbivores; e.g., grazing by the gastropod Littorina obtusata induces a defense response in the brown alga Fucus vesiculosus, reducing palatability to several other grazer species [22]. There has not yet been a seagrass example of such trait-mediated grazer-grazer interaction through induction of a defense response; however, simulated grazing induces a compensatory growth response in the seagrass Posidonia oceanica [23] and grazing by urchins can increase phenolic compounds in Thalassia testudinum and Halodule wrightii [24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ability to induce anti-herbivory traits in response to grazing by mesoherbivores has been repeatedly shown for different F. vesiculosus populations (e.g. Hemmi et al, 2004;Rohde et al, 2004;Long et al, 2007;Yun et al, 2007;Yun et al, 2012).…”
Section: Introductionmentioning
confidence: 90%
“…Regulation of genes involved in photosynthesis in Fucus vesiculosus after 15 and 18 days of isopod grazing. Identification of differentially expressed genes as well as calculation and interpretation of fold changes (FCs) as described for differences in food quality (see also Rohde et al, 2004;Long et al, 2007). Defences were first detectable 18 days after onset of grazing.…”
Section: Dynamics In Anti-herbivory Defencesmentioning
confidence: 99%
“…Competitively dominant animals are often those with the greatest capture rate, which are able to use more or higher quality resources than their neighbor. Capture rate by mobile grazers may be determined by species mobility, territoriality, or foraging choices such that competitive outcomes may depend on a species' ability to defend a resource (Robertson 1996), switch among resources (Wilson and Yoshimura 1994), or withstand prey defences (Long et al 2007). Moreover, plants are sessile and constrained to the resource v www.esajournals.org and competitive conditions in which they germinate.…”
Section: Introductionmentioning
confidence: 99%